Curing Disability in Contemporary Russia: Rehabilitation Practices and the Placebo Effect - Klepikova, Anna (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2019)
The paper is based on the materials of an ethnographic research project involving interviews with parents of children with developmental disabilities, primarily intellectual disabilities, multiple disabilities, and autism. Though in contemporary humanistic pedagogy and psychology developmental disabilities are viewed in terms of difference and diversity, Russian public and professional discourse on disability is dominated by a medicalised approach and the majority of parents adhere to this view. This article analyses the patterns of rehabilitation and treatment of children with disabilities in the family context. It views the effectiveness of various popular therapies offered to children with disabilities through the lenses of the placebo effect theory. It shows that the assessment of both biomedical and alternative treatment outcomes by parents of children with disabilities are subject to the placebo effect, and this effect is maximized by various symbolic elements of treatment, such as price, prestige, or popularity of a certain drug, method or institution. The placebo effect, together with other factors, accounts for the commercialization of the disability services sphere.
24 cm
Keywords: disability; developmental disabilities; autism; medicalisation; Biomedicine; alternative medicine; placebo effect